Analysis of Factors Affecting Fraudulent Financial Statements with Hexagon Theory Fraud Indicators : Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period - Fitriani, Nur; Ria; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to empirically examine the impact of false financial statements on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021 using indicators from the hexagon fraud theory. Purposive sampling techniques were used to select samples for this investigation, which used 130 samples. The analysis used was multiple linear regression analysis in this study with SPSS software version 25. The F-SCORE assessment is used in measurement to assess financial statement fraud. Based on research findings, financial statement fraud is positively influenced by outside pressure, political connections, the nature of the industry, auditor turnover, and CEO dualism. Variable changes do not influence financial statement fraud in directors. This study shows how several indicators of the hexagon fraud theory can influence the likelihood of fraud. The study's findings are anticipated to be taken into account by the company in the future so that it can monitor all departments to guard against this fraud.